1994
DOI: 10.1111/j.1398-9995.1994.tb02093.x
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of ELISA for IgG subclass antibodies against inhalant antigens in early childhood

Abstract: ELISA is increasingly used to measure antibodies in new circumstances. Recently, it has been applied to the measurement of IgG subclass antibodies against common antigens in early childhood. These studies have raised concerns about the specificity of some of these assays. This paper details the results of experiments which have assessed the specificity of IgG1 binding to allergens of dust mite (Dermatophagoides pteronyssinus) and ryegrass (Lolium perenne) pollen by inhibition ELISA in the sera of 2-year-old ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…As to the humoral response, several early studies clearly show that the IgG response is elevated in atopics (9)(10)(11)(12)(13). However, some authors claim that specific IgG antibodies against mites early in life occurs regardless of atopic status (8). The basis for this discrepancy (presence of IgG antibodies in both atopics and non-atopics) is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to the humoral response, several early studies clearly show that the IgG response is elevated in atopics (9)(10)(11)(12)(13). However, some authors claim that specific IgG antibodies against mites early in life occurs regardless of atopic status (8). The basis for this discrepancy (presence of IgG antibodies in both atopics and non-atopics) is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In non-atopic subjects, the involvement of the specific immune response to inhalant allergens is less clear. Some studies have found specific allergen antibodies (8) while other have failed to do so or found much lower 208 amounts (9)(10)(11)(12)(13). Here we scrutinised the antibody specific IgG responses to birch pollen, a widely spread and important inhalant allergen in Sweden, in sibling pairs discordant for atopy.…”
mentioning
confidence: 99%